Growth and Yield Responses of Red Onions to Different Nutrient Availability in Fertigation System - Brotodjojo, R.R. Rukmowati; Padmini, Oktavia S.; Pratomo, Awang H. (RSF Conference Series: Engineering and Technology, 2022)
Nutrient availability affected plant growth and yield. This study aimed to examine the effect of interval application and fertigation frequency toward plant growth and yield, and further determined the most proper fertigation interval and frequency that support the highest plant growth and yield. Experiment was arranged in Split plot randomized Completely Block Design. The main plots were interval of nutrient application, i.e., 3 days interval, 6 days interval, 9 days interval. The sub plots were the frequency of nutrient application, i.e., once/day, 2 times/day, 3 times/day. The plot size for each treatment was 2.5 m×1.3 m and plant spacing was 15 cm×20 cm. Space between beds was 1 m. Red onions (Bima variety) were planting in a raised bed covered with silver black polythene mulch. Before planting, 5 ton/ha manure and 1 ton/ha lime were mix with the soil. Fipronil 1.5% was applied with dose 8 kg/ha to control grubs. Nutrient was mixture between liquid organic fertilizer (7.5 mL/L), rabbit urin (5mL/L) and AB Mix (7.5 mL/L A+7.5 mL B). The nutrient was dispensed 150 mL/plant according to treatment using fertigation system operated remotely using Internet of Things. The nutrient was given from 14 DAP (Days After Planting) until 68 DAP. Irrigation water was dispensed 150 mL daily in the same way. The interval of fertigation significantly affected the growth of red onion (plant height, number of leaves and number of yield). Three days interval of nutrient supply resulted in the tallest plant, highest number of plant leaves, and highest number of bulbs. However, the frequency of nutrient supply daily significantly affected the yield of red onion. The application of nutrient three times/day provided the highest yield (economical dry weight). Further research to examine the effect of fertigation of red onion quality is required.